2005
DOI: 10.1063/1.2009833
|View full text |Cite
|
Sign up to set email alerts
|

Determination of thermal and optical parameters of melanins by photopyroelectric spectroscopy

Abstract: ReceivedPhotopyroelectric spectroscopy (PPE) was used to study the thermal and optical properties of electropolymerized melanins. The photopyroelectric intensity signal and its phase were independently measured as a function of wavelength, as well as a function of chopping frequency for a given wavelength in the saturation part of the PPE spectrum. Equations for both the intensity and the phase of the PPE signal were used to fit the experimental results. From the fittings we obtained for the first time, with g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…In PPS, a true absorption coefficient can be measured in even heavily scattering solid samples. de Albuquerque et al (2005Albuquerque et al ( , 2006 showed only a discontinuity in the absorption at 1.7 eV, which suggests that a dominant component within the 'system' has a HOMO-LUMO gap at that energy. Their data are consistent with the calculated HOMO-LUMO gap of indolequinone (IQ see Figure 1), the 2-electron oxidation product of DHI (or indeed DHICA), which is thought to be a significant component of the macromolecule.…”
Section: Optical Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PPS, a true absorption coefficient can be measured in even heavily scattering solid samples. de Albuquerque et al (2005Albuquerque et al ( , 2006 showed only a discontinuity in the absorption at 1.7 eV, which suggests that a dominant component within the 'system' has a HOMO-LUMO gap at that energy. Their data are consistent with the calculated HOMO-LUMO gap of indolequinone (IQ see Figure 1), the 2-electron oxidation product of DHI (or indeed DHICA), which is thought to be a significant component of the macromolecule.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…If a fundamental gap does exist then absorption (either in solution or in solid state) is not an appropriate tool to detect and measure it. Recent photopyroelectric spectroscopy (PPS) measurements indicate that there may indeed be some fundamental energy gap in eumelanins at 1.7 eV (the near infrared consistent with eumelanin 'blackness') (de Albuquerque et al, 2005(de Albuquerque et al, , 2006. In PPS, a true absorption coefficient can be measured in even heavily scattering solid samples.…”
Section: Optical Absorptionmentioning
confidence: 99%
“…The detected signal V͑ , t͒ is proportional to the pyroelectric coefficient p of the detector and to the temperature distribution along the detector thickness: 15,16,18,19,22,23 …”
Section: Mandelis-zver Theoretical Model "Ppes…mentioning
confidence: 99%
“…[10][11][12][13] Among the PTS techniques, photoacoustic spectroscopy ͑PAS͒, 14 which is the most traditional one, and the more recent photopyroelectric spectroscopy 15 ͑PPES͒ have been used for studying thermal and optical properties of polymeric films and semiconductors. [16][17][18][19][20][21][22][23][24] In these techniques a pulsed light beam is absorbed in a solid sample and the converted heat diffuses into the bulk structure; the sample expansion, or the temperature gradient, is then detected by an appropriate sensor system. The detected signal depends on the optical and thermal properties of the sample: the optical absorption coefficient ␤͑͒ ͑ being the light wavelength͒, the nonradiative conversion efficiency ͑͒, the thermal conductivity k, and the thermal diffusivity coefficient ␣.…”
Section: Introductionmentioning
confidence: 99%
“…The photopyroelectric intensity signal and its phase were independently measured as a function of wavelength and chopping frequency for a given wavelength in the saturation part of the PPE spectrum. The thermal diffusivity coefficient, thermal conductivity, the specific heat of the samples, and a value for the condensed phase optical gap could be obtained [24]. Thermal properties, such as thermal conductivity, thermal diffusivity, thermal effusivity and specific heat capacity, of geometrically frustrated multiferroic ErMnO 3 , having range of grain sizes from 32 to 220 nm has been measured by the photopyroelectric technique [25].…”
Section: Introductionmentioning
confidence: 99%